AUTOIMMUNE LIVER DAMAGE IN PATIENT WITH LYELL`S SYNDROME - Елена Анатольевна Талицкая; Алексей Анатольевич Близнюк; Ольга Константиновна Саблина; Светлана Владимировна Калитина (Медицина в Кузбассе)
Autoimmune hepatitis (AIH), primary biliary cholangitis (PBC), primary sclerosing cholangitis (PSC) are independent liver diseases. But in some cases, patients have syndromes of several liver disease. Overlap-Syndrome sclerosing cholangitis / autoimmune hepatitis by definition from EASL recommendation is ill-defined immune disorders with characteristic histological features of autoimmune hepatitis and typical cholangiographic signs of sclerosing cholangitis. Patients with overlap-syndrome sclerosing cholangitis / autoimmune hepatitis in 1,4-17 % cases.